Purification of AZ80 and Degassing of AZ91 Alloy by Ultrasonic Treatment - Zheng Jia; Bing Yu; Yongzhi Yu (Crystals, 2022)
The effects of ultrasonic power, treatment time and holding time on AZ80 magnesium melt purification by ultrasonic field were studied. The results indicate that ultrasonic treatment can accelerate the separation of inclusions and attain melt purification. When the magnesium alloy melt is treated with ultrasonic power 80 W at 650 °C for 60 s and holding 100 s, the best melt purification is achieved. Moreover, the effect of ultrasonic degassing on AZ91 alloy was also investigated. When the ultrasonic power is 150 W for 90 s, the hydrogen content and degassing efficiency are 9.6 cm3/100 g and 50.5%, respectively. The corresponding mechanical properties are Rm = 194 MPa, R0.2 = 133 MPa and A = 4.8%, respectively, and the mechanisms of purification and degassing were analyzed because of the cavitation effect.